1970
DOI: 10.1037/h0029641
|View full text |Cite
|
Sign up to set email alerts
|

Verbal conditioning and therapeutic change.

Abstract: The present study was undertaken to investigate the generalization of verbal conditioning effects to postconditioning personality and behavioral measures. Psychiatric 5s were given social reinforcement following positive self-references during eight 30-minute weekly therapy-type sessions. A Yoked-Control group received exactly the same reinforcement delivered noncontingently. Generalization was evaluated by change on semantic differential concepts, Taylor Manifest Anxiety scale score, and ward behavior ratings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…It has been repeatedly pointed out that the validity of verbally oriented conditioning in counseling can be considerably strengthened if it can be shown to generalize to other response classes-both within the interview and beyond the consulting room (Krasner, 1965;Williams, 1964). Support for this notion has been found through experimental test by Lapuc and Harmantz (1970) and Hoffnung (1969). For the present studies, it was hypothesized that selected nonlinguistic behaviorstotal length of utterance and the duration of utterance-would be influenced by the experimental variables.…”
mentioning
confidence: 78%
“…It has been repeatedly pointed out that the validity of verbally oriented conditioning in counseling can be considerably strengthened if it can be shown to generalize to other response classes-both within the interview and beyond the consulting room (Krasner, 1965;Williams, 1964). Support for this notion has been found through experimental test by Lapuc and Harmantz (1970) and Hoffnung (1969). For the present studies, it was hypothesized that selected nonlinguistic behaviorstotal length of utterance and the duration of utterance-would be influenced by the experimental variables.…”
mentioning
confidence: 78%
“…2 This and the original paper have not innovated by pointing to the close link between self-processes and the dynamics and outcomes of therapy. That the self remains a dominant object of concern and research in clinical psychology is demonstrated by the very recent studies by Braucht (1970), Carlson (1970), Long, Ziller, andBankes (1970), Truax, Schuldt, andWargo (1968), and Lapuc and Harmatz (1970), among others. How can this body of scientific work be thrown out of the window with the nonchalant assertion that it is "philosophical?"…”
mentioning
confidence: 98%
“…Within the context of these verbal operant studies it has been noted that in order for the paradigm to be considered viable not only should conditioning be detectable, but also that there should be some noticeable generalization, namely (a) to situations outside the conditioning setting and (b) to other related behaviors within the setting (Williams, 1964). Previous research has shown that both of these conditions tend to obtain from conditioning studies (Lapuc & Harmatz, 1970).…”
mentioning
confidence: 99%